Dynamic clustering of multivariate panel data - André Lucas; Julia Schaumburg; Bernd Schwaab (Tinbergen Institute, 2020)
We propose a dynamic clustering model for studying time-varying group structures in multivariate panel data. The model is dynamic in three ways: First, the cluster means and covariance matrices are time-varying to track gradual changes in cluster characteristics over time. Second, the units of interest can transition between clusters over time based on a Hidden Markov model (HMM). Finally, the HMMâ exteuro™s transition matrix can depend on lagged cluster distances as well as economic covariates. Monte Carlo experiments suggest that the units can be classified reliably in a variety of settings. An empirical study of 299 European banks between 2008Q1 and 2018Q2 suggests that banks have become less diverse over time in key characteristics. On average, approximately 3% of banks transition each quarter. Transitions across clusters are related to cluster dissimilarity and differences in bank profitability.
Keywords: G21; C33; 330; dynamic clustering; panel data; Hidden Markov Model; score-driven dynamics; bank business models